2008
DOI: 10.1080/01635580701630487
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Factor Analysis of Squamous Cell Carcinoma of the Esophagus in Uruguay

Abstract: In the period 1996--2004, a hospital-based, case-control study on diet and risk of squamous cell carcinoma of the esophagus was conducted in Montevideo, Uruguay. The study included 234 cases and 468 controls, frequency matched on age, sex, and residence. Factor analysis (principal components) was used to identify the major food patterns associated with esophageal cancer. The analysis of food groups led to the identification of four patterns, arbitrarily labeled as traditional, healthy, high-fat, and drinker. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 40 publications
3
51
1
Order By: Relevance
“…19 Also the prudent pattern was strongly protective in these studies, since loaded on fish, raw vegetables and fruits. 20,21 In this study, gastric cancer was inversely associated with the prudent pattern and positively associated with the traditional pattern. Both the drinker and Western patterns were not associated with this malignancy.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…19 Also the prudent pattern was strongly protective in these studies, since loaded on fish, raw vegetables and fruits. 20,21 In this study, gastric cancer was inversely associated with the prudent pattern and positively associated with the traditional pattern. Both the drinker and Western patterns were not associated with this malignancy.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies on this cancer site through factor analysis were conducted in Sweden 20 and Uruguay. 21 Both studies showed that the drinker pattern was associated with increased risk. In fact, this finding is expected since alcohol drinking is a strong risk factor in Adjusted for age, residence, urban/rural status, education, body mass index, smoking status, years since stopping, number of cigarettes/ day among current smokers, total energy intake and all the dietary patterns.-2 Main food groups for the traditional pattern: total grains, all tubers.-3 Upper aerodigestive tract (oral cavity, pharynx, oesophagus, larynx).…”
Section: Discussionmentioning
confidence: 99%
“…The factor rotation selected for this research was the same as those reported in previous studies on dietary pattern analysis that used factor analysis or principal component analysis: the orthogonal varimax 34,5,6,37,38,39,40 , the oblique promax 11,12,13,14,15 and direct oblimin 16,17 . In brief, the varimax is a type of orthogonal rotation that attempts to maximize the variance of squared loadings on a factor, i.e., to reduce the cross-loadings of the variables, leading to uncorrelated simple factor structures 41 .…”
Section: Food Groups Food Itemsmentioning
confidence: 99%
“…Orthogonal rotation leads to uncorrelated factors that are considered simpler and easier to interpret 8,10 , whereas nonorthogonal (oblique) rotation, such as promax and oblimin, allow producing correlated factors which are considered harder to interpret and, for this reason, have been used less in studies involving dietary pattern analysis 11,12,13,14,15,16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…An increased risk of oesophageal squamous cell carcinoma was observed with the western pattern (high: second median v. low: first median, OR 5 10? 13, 95 % CI 8?45, 43?68). …”
mentioning
confidence: 99%